Effect of nitric oxide on the preterm neonatal rabbit ductus arteriosus cystathionine-γ-lyase/hydrogen sulfide pathway - Liu, Wen-long (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: To investigate the impact of sodium nitroprusside (a nitric oxide donor) in the ductus arteriosus in preterm rabbits on hydrogen sulfide (H(2)S)-cystathionine-γ-lyase (CSE) system